The underutilization factors of computerised accounting software among accountants - Nur Fatiha Na’aimah, Mohd Fauzi (2022)
Nowadays, computerized accounting software (CAS) is a must tool to have for every business operation specifically in the accounting department. It is not deniable that the accounting software has contribute a lot of benefits to the users and business owners. Prior research also has shown that the advantages of the computerized accounting system has helped to improve the efficiency and boost the business performance. However, a little research was conducted to study the underutilization factors of computerized accounting software among accountants which are believed are the challenges encountered by the accountants in their daily basis. This study was intended to cover that area by adopting technology-organization-environment (TOE) framework. The objective of this study is to examine the relationship between lack of awareness on internal control features (technological context), lack of management support (organizational context) and external pressure from software industries (environmental context) towards the underutilization factors of CAS among accountants. This study used a quantitative approach where a total number of 108 questionnaires were distributed among accountants. The returned questionnaires were analyzed by using PLS-SEM and the results show that only lack of awareness on internal control features have a significant relationship towards underutilization factors of CAS. Lastly, implications of the outcomes, potential limitations, and recommendations for future research are also discussed in this study